2017
DOI: 10.11591/ijece.v7i5.pp2706-2712
|View full text |Cite
|
Sign up to set email alerts
|

Link Aggregation Control Protocol on Software Defined Network

Abstract: A physical connection of computer network must be made reliably. Breaking connection will cause communication between nodes (for example routers, switches, hosts) can be disconnected. One of the solutions is implemention of link aggregation (LA). LA integrates several of physical ports together to make a single logical communication link. Accordingly, there is load sharing traffic among the member port of the group, high-throughput increasing via a single link, and redundancy providing for broken links. We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…Also in research [23] and [24] the researchers used ONOS controller in mininet software to studies the bandwidth in SDN. The throughput has been tested for linear topology network on using by used link aggregation method [25].In the research [26] TCP observed to evaluate the load balance in data center SDN. There are also further researches that evaluate SDN networks regarding their use of firewall deployment settings [14,16,[27][28][29][30].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Also in research [23] and [24] the researchers used ONOS controller in mininet software to studies the bandwidth in SDN. The throughput has been tested for linear topology network on using by used link aggregation method [25].In the research [26] TCP observed to evaluate the load balance in data center SDN. There are also further researches that evaluate SDN networks regarding their use of firewall deployment settings [14,16,[27][28][29][30].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Outra solução analisada como um método para recuperação rápida em caso de falhas correspondeà implementação da agregação de enlaces por meio do uso do LACP [7], sendo possível integrar várias portas físicas em conjunto para criar umúnico enlace lógico de comunicação.…”
Section: Trabalhos Relacionadosunclassified
“…Artigos relacionados como [3], [6] e [7] analisam o tempo de recuperação dos métodos de resiliência e de seus respectivos mecanismos, porém não fazem uma análise de desempenho da rede de forma mais profunda. Assim, neste artigoé realizada uma análise de desempenho da rede quantificando o jitter e a perda de pacotes em cenários com falha.…”
Section: Trabalhos Relacionadosunclassified
See 1 more Smart Citation
“…By using SDN technology, congestion control utilizes the global knowledge of the network in its decision making. Data monitoring collects network information, and this information is used by the controller to make centralized decisions in response to changing network conditions [22]. This approach produces accurate information so that the sender's sending rate can be customized appropriately according to network conditions.…”
Section: Figure 1 Router Assisted Congestion Controlmentioning
confidence: 99%